2003
DOI: 10.1002/jcla.10060
|View full text |Cite
|
Sign up to set email alerts
|

Indices of obesity, dyslipidemia, and insulin resistance in apparently healthy Caribbean subjects

Abstract: Reports from developing countries indicate that a rise in the socioeconomic level is a risk factor for metabolic disorders. We aimed to assess the indices of obesity, dyslipidemia, and insulin resistance among fairly literate healthy adults in a multidisciplinary institution in Trinidad. The study included 156 volunteers (46 males and 110 females, 17-40 years old). The subjects provided information on age, ethnicity, educational attainment, and occupation in self-administered, closed-ended questionnaires. Wais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In this study sample, no statistical significant difference was found in body mass index between women and men, which is in agreement with previous studies [15][16][17] . In other report, body mass index was demonstrated to be influenced by gender 18 .…”
Section: Discussionsupporting
confidence: 93%
“…In this study sample, no statistical significant difference was found in body mass index between women and men, which is in agreement with previous studies [15][16][17] . In other report, body mass index was demonstrated to be influenced by gender 18 .…”
Section: Discussionsupporting
confidence: 93%
“…The estimated economic burden of diabetes and hypertension in 2001 was US$754 million in Trinidad and Tobago (Barcelo et al 2003, Caribbean Commission on Health and Development [CCHD] 2006). The burden of chronic disease continues to escalate with the increasing prevalence of metabolic syndrome components such as obesity, dyslipidemia, and insulin resistance (Sargeant et al 2001, Ezenwaka and Kalloo 2003, Ezenwaka et al 2007). In the Caribbean, obesity has increased at an alarming rate of almost 400% in 20 years and is accompanied by increasing rates of mortality from diabetes and hypertension (Henry 2006, CCHD 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Countries throughout the world have experienced a marked increase in the prevalence of overweight and obese children and adolescents (4, 5). The increase in the prevalence of overweight and obesity implies a substantial increase among children and adolescents (13) in lifestyle‐associated diseases such as type 2 diabetes (6, 7), dyslipidemia (8, 9), hypertension (10, 11), coronary heart disease (12), and stroke, which are usually found in adults (14, 15).…”
Section: Introductionmentioning
confidence: 99%